From data to action – the Focus Forward methodology: a participatory, multistakeholder approach for solution prioritization and action plan development - Hoet, Armando E.; Matos, Alice; Calderón, Ericka; Rodríguez, Clara Marcela (Frontiers in Education, 2026)
IntroductionAs global conditions change, graduates require a new set of skills. Consequently, universities must review their curricula and teaching methods to adapt to this evolving landscape. This requires intentional and organized efforts, which are best supported by well-structured action plans. While creating action plans is a common practice and there has been progress in improving their development, there is still a lack of systematic and collaborative approaches described in the literature to address the needs of higher education institutions.MethodsThis methods paper describes the Focus Forward methodology - a participatory and multistakeholder approach for action plan development. This methodology is centered around a 1.5-day workshop to socialize evidence of the problems to be addressed, to analyze the root causes of such problems, and to identify and prioritize potential innovative solutions to address such causes. To ensure thorough preparation and effective execution of the workshop, this methodology is operationalized through three major stages including Workshop Planning, Workshop Implementation, and Action Plan Writing, thoroughly described in this manuscript.ResultsThis methodology has been implemented in five different settings to date. To illustrate each step, we provide real-life examples drawn from across these five implementations, highlighting key differences between them.DiscussionThe FF methodology is in alignment with many good practices identified previously in the literature which focused on maximizing the potential of a participatory multistakeholder workshop for the development of purposeful action plans. This methodology has proven to be both scalable and adaptable, supporting organizations, higher education institutions and beyond, navigating complex challenges.